Promoting social justice through the scholarship of teaching and learning - Liston, Delores D.; Rahimi, Regina, 1971- (Scholarship of teaching and learning., 2017)
Although the contributors work in a variety of disciplines and employ different theoretical frameworks, they are united by the conviction that education should improve our lives by promoting equity and social justice.